PENGARUH KARAKTERISTIK DEWAN DAN KOMITE AUDIT TERHADAP TANGGUNG JAWAB SOSIAL PERUSAHAAN - Maura Indira; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2022)
The purpose of the study entitled "The Effect of Board and Audit Committee Characteristics on Corporate Social Responsibility" is to determine the effect of board and audit committee characteristics on corporate social responsibility (CSR) in companies listed on the Indonesia Stock Exchange. In this study, information assortment was completed utilizing the documentation technique. The information required is gotten by gathering data from Financial statement in the Indonesia Stock Exchange. The statistical population of this study are all companies listed on the Indonesia Stock Exchange and the research period is from 2015 to 2020. Using a purposive sampling technique, a sample of 55 companies was selected. Multivariate regression and Eviews 9 software were used for data analysis and hypothesis testing. The results showed that board size had a significant effect on CSR, board independence had a significant effect on CSR, managerial ownership had a significant effect on CSR, duality had a significant effect on CSR audit committee size had no significant effect on CSR and the financial expertise of audit committee members has a significant effect on CSR.